Aproveitamento alimentar de jambolão - Soares, Jackeline Cintra (2015)
The fruits are known to be natural sources of antioxidants, among which are Vitamin C and E, carotenoids and phenolic compounds responsible for the prevention of various diseases in humans when consumed. But some fruit species are little known / exploited so little advantage. The objective of this study was to evaluate the morphology, nutritional quality, sensory and functional, technological point of view, the use of fruit jambolan in the production of pulp for the production of nectar and sherbets. The samples were collected in 5 different regions (Region 1 – North, Region 2 - South, Region 3 - Center, Region 4 – East and Region 5 - West) in Goiânia-GO, and were later processed into pulp for generation of products. For the morphological and physical analysis were selected 60 fruits (60 repetitions) of each region and conducted correlation analysis between physical and morphological properties of the fruit, after the fruits analyzes were pulped, and the pulps of each region were divided into 4 lots (4 repetitions) for physical analysis, chemical, bioactive compounds and chemical composition. The analyzes were performed on 4 replications and in triplicate. For product formulations simplex experimental design was used, varying the concentrations of water, sugar and jambolan pulp for nectar. For sherbets varied concentrations of milk, sugar and jambolan pulp. Through the physical, chemical and technical characteristics on the products could be performed to determine the influence of these ingredients in each formulation. The greatest desirability formulation was determined by the desirability test, compared with a commercial product, and using the sensory analysis of each product. Confronted the predicted results with those analyzed, the greater desirability formulation, validating the model chosen. Characterized the most desirable formulation as its chemical composition and the content of bioactive compounds. The results indicated the correlation analysis, there is a strong positive correlation above 80%, among the largest diameter (D1), smaller diameter (D2), length (H1) and fruit volume (VF) with the fruit mass (MF). The color of jambolan pulps are related to the degree of fruit ripening by changing the content of anthocyanins, and the pulp of fruits jambolan and highlighted as a source of anthocyanins and vitamin C. jambolan pulp showed high humidity and low in lipids. Sherbets showed non-Newtonian and pseudoplastic behavior, and the model that best fit was the Herschel-Bulkley model. The influence of ingredients in the formulations of sherbets indicated that high levels of sugar are related to increased melt rate, elasticity, cohesiveness and brightness. The consumption of sherbets jambolan can be recommended due to the nutritional value and the presence of phenolic compound (96.86mg eq. AG mg-1). AT, SST, SST / AT, color and VA changed according to variations in ingredients in nectars formulations. The nectar jambolan showed high content of phenolic compounds (104.70mg Eq. AG g-1) and high antioxidant capacity and may offer health benefits.